A Cluster of Novel Coronavirus Disease 2019 Infections Indicating Person-to-Person Transmission Among Casual Contacts From Social Gatherings: An Outbreak Case-Contact Investigation. (12th June 2020) - Shen, Ye; Xu, Wenjie; Li, Changwei; Handel, Andreas; Martinez, Leonardo; Ling, Feng; Ebell, Mark; Fu, Xiaofei; Pan, Jinren; Ren, Jiangping; Gu, Weiling; Chen, Enfu
Abstract: Background: Severe acute respiratory syndrome coronavirus 2, the pathogen causing novel coronavirus disease of 2019 (COVID-19), efficiently spreads from person to person in close contact settings. Transmission among casual contacts in settings such as during social gatherings is not well understood. Methods: We report several transmission events to both close and casual contacts from a cluster of 7 COVID-19 cases occurring from mid-January to early February 2020. A total of 539 social and family contacts of the index patient's, including members of a 2-day wedding and a family party, were contacted and screened through epidemiologic surveys. The clinical progression of all cases is described. Results: We estimate the secondary attack rate among close contacts to be 29% (2 of 7) and for the casual contacts to be 0.6% (3 of 473). The incubation period of our case cluster was 4–12 days (median, 7 days). Conclusions: Transmission efficiency among close contacts was higher than among casual contacts; however, transmission from second-generation cases may help spread the virus during the incubation period.